Effect of honeybee (Apis cerana indica) pollination on seedset and yield of buckwheat (Fagopyrum esculentum) - RAHMAN, A; RAHMAN, S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1993-95 to investigate the effect of honeybee (Apis cerana indica) on seed set and yield of buckwheat (Fagopyrum esculentum L.). Buckwheat spike/plant, seeds/spike. Percentage of filled seed and weight of grain were found to be higher in bee pollinated treatment over open and self pollination. There was signigicant difference in yield in bee pollinated treatment over open and without bee pollinated treatments. The foraging activityÂ of A. indica showed maximum number was recorded during 15.00 to 16.00 pm having 0.8 forager on the crop.